2020
DOI: 10.3389/fimmu.2020.01188
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of T-Cell Responses to Aquaporin-4 and Myelin Oligodendrocyte Glycoprotein in Inflammatory Demyelinating Central Nervous System Diseases

Abstract: Hofer et al. AQP4 and MOG Specific T-Cell Responses 1.50-58.02) and DRB1 * 03 (OR = 6.75, 95% CI = 1.19-38.41). Furthermore, HLA DRB1 * 01 was also associated with the presence of AQP4 p156-170 reactive T-cells (OR = 31.67, 95% CI 1.30-772.98). To summarize, our findings suggest a role of AQP4-specific, but not MOG-specific T-cells, in NMOSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…Antigen‐specific T cells in NMOSD and MOGAD have been seldom detected despite central dogma for the necessity of these cells in their role for autoantibody production and pathogenicity. Interestingly, AQP4‐specific CD4 + T cells were detected in AQP4 Ab‐positive patients, with T cell reactivity observed in a peptide sequence at amino acids 156–170 which overlaps with the epitope recognised by AQP4 Ab 113,114 . Contrastingly, the same study could not detect MOG‐specific T cells in MOG Ab‐positive patients and this was postulated to be because of the failure of synthetic peptides in mimicking antigen processing and MHC presentation 113 .…”
Section: Pathogenic Mechanisms In Autoimmune Demyelinationmentioning
confidence: 91%
See 2 more Smart Citations
“…Antigen‐specific T cells in NMOSD and MOGAD have been seldom detected despite central dogma for the necessity of these cells in their role for autoantibody production and pathogenicity. Interestingly, AQP4‐specific CD4 + T cells were detected in AQP4 Ab‐positive patients, with T cell reactivity observed in a peptide sequence at amino acids 156–170 which overlaps with the epitope recognised by AQP4 Ab 113,114 . Contrastingly, the same study could not detect MOG‐specific T cells in MOG Ab‐positive patients and this was postulated to be because of the failure of synthetic peptides in mimicking antigen processing and MHC presentation 113 .…”
Section: Pathogenic Mechanisms In Autoimmune Demyelinationmentioning
confidence: 91%
“…Interestingly, AQP4-specific CD4 + T cells were detected in AQP4 Ab-positive patients, with T cell reactivity observed in a peptide sequence at amino acids 156-170 which overlaps with the epitope recognised by AQP4 Ab. 113,114 Contrastingly, the same study could not detect MOG-specific T cells in MOG Ab-positive patients and this was postulated to be because of the failure of synthetic peptides in mimicking antigen processing and MHC presentation. 113 Indeed, a previous study using Escherichia coli-expressed MOG coupled to fluorescent beads was able to detect MOG-specific CD4 + T cells producing IFNgamma, IL-22 and IL-17A in 16 out of 29 MS patients.…”
Section: T Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, patients seropositive for both AQP4 and MOG antibodies have been reported when detecting MOG-Abs by ELISA, while double seropositivity is not common when utilizing CBAs (41). Moreover, whether MOG antigen or MOG-Abs participate in NMOSD pathogenesis is needed to be further clarified, as one recent research has found that a role of AQP4-specific, but not MOG-specific T-cells, in NMOSD (51).…”
Section: Mog-abs In Neuromyelitis Optica Spectrum Disordermentioning
confidence: 99%
“…Intracortical demyelination was overrepresented in comparison to classical MS [ 47 ]. These pathological observations have to be contrasted with the fact that, to date, no MOG-specific T cells have been found in the peripheral blood of patients with MOGAD [ 48 ]. This could be explained by the fact that these MOG-specific T cells are difficult to detect due to their low frequencies.…”
Section: Immunopathogenesismentioning
confidence: 99%